Non sex-related subtotal rupture of the corpus cavernosum without urethral injury: A case report and literature review - Bayraktar, Zeki; Albayrak, Selami (Edizioni Scripta Manent s.n.c., 2016)
Although penile fracture is a rare case, it is a well-described urologic emergency. It results from the rupture of the tunica albuginea of corpora cavernosa by blunt strain that commonly mandates immediate surgical exploration. Urethral injury may also accompany penile fracture. An ideal anamnesis and a special physical examination were determinant to achieve a correct diagnosis. It is usually diagnosed based on clinical examination, but ultrasonography can be very helpful in diagnosis. The treatment is based on the presence of associated urethral injury. Early surgery is preferable to conservative management, because it is associated with better outcomes and fewer long-term complications. The surgical repair of cavernous body can produce good results, with a favorable prognosis and minimal rate of complications. We present a penile fracture case of 34-year-old with subtotal rupture of the right corpus cavernosum without urethral injury who treated by early surgery and good results.
Keywords: Diagnosis; Penile Fracture; Rupture; Surgery; Treatment